Political Communication Strategy of the Regional Head in Managing Government in North Gorontalo Regency - Djuyandi, Yusa (Jurnal Bina Praja, 2017)
Since elected as the Regent of North Gorontalo period of 2013-2018, various programs, especially with regards to improving the welfare of the people, have been done well by Indra Yasin so far. The success of development in North Gorontalo District is considered inseparable from the political communication capabilities undertaken by the regents in managing the government. Political communication strategy undertaken by Indra Yasin in managing government becomes important to analyze. This study used qualitative methods, in which the source of primary data obtained from interviews and observations, while secondary data obtained from the study of documentation and the Recent studies from literature. From the results of this research, the political communication strategies were undertaken by Indra Yasin in managing government were built through nurturing characters, strengthening political institutions, to promote unity and consensus building. The success in building a strategy of political communication, in the end, was able to bring the support from various elements of government, politics, and society to development programs that have been planned.